ANALISIS PENGARUH BRAND AWARENESS DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DENGAN BRAND ATTACHMENT SEBAGAI VARIABEL MEDIASI (Survei pada Pelanggan PT Indiva Media Kreasi) - Y. Djoko Suseno, Yeni Mulati, Alwi Suddin & (Universitas Slamet Riyadi, 2017)
This research aims to determine the effect of brand awareness andbrand image, either directly or through the mediation of brand attachment tothe purchasing decision of customers of PT Indiva Media Kreasi. Thepopulation in this research are active customers of PT Indiva Media Kreasi inthe period August 2015 to August 2016. The total population are 980customers. Samples were taken based on random sampling of 10% of thepopulation, namely 98 and rounded to 100 customers. Data collectiontechniques using questionnaires through validity and reliability test.Mechanical analysis through path analysis (path) with the classicalassumption. Validity of test results, research instruments of variable brandawareness, brand image, brand attachment and consumer purchasingdecisions valid. Reliability test results are reliable. From the classicassumption test, multicollinearity test pass the test, heteroscedasticity testpass the test, autocorrelation test pass the test, and normality test pass thetest. The analysis showed that brand awareness and brand imagesignificantly influence brand attachment. Brand awareness and brand imageindirectly influence the purchase decision. Brand attachment significantlyinfluence purchasing decisions. Brand attachment mediates the effect ofbrand awareness and brand image on purchasing decisions.Keywords: brand awareness, brand image, brand attachment, purchasedecision.